2007
DOI: 10.1007/s00244-007-9025-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biological and Technical Factors on Brain and Muscle Cholinesterases in Nile Tilapia, Oreochromis niloticus: Implications for Biomonitoring Neurotoxic Contaminations

Abstract: Influence of body length, body weight, gender, sexual maturity, and tissue storage on brain and muscle cholinesterases (ChE) in Nile tilapia was evaluated considering its potential use in biomonitoring neurotoxic contaminations in tropical environments. Results show that ChE activities in both tissues decreased significantly with increased total length (4-24.5 cm) or body weight (1-186 g) of the fish and the relationships were curvilinear. Comparisons of the slopes and elevations of the regression lines of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…The results revealed that responses of brain and muscle ChE, hepatic EROD and GST activities, bile PAHs of Nile tilapia and hepatic MT can be used as biomarkers in assessing pollution status and pollution trends in water resources in Sri Lanka. In the present study, limited size range of Nile tilapia was used in biomarker studies as the body size could influence some biomarker measurements (Pathiratne et al 2008). Gender specific differences in the tested biomarkers in Nile tilapia were not evident in the present study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results revealed that responses of brain and muscle ChE, hepatic EROD and GST activities, bile PAHs of Nile tilapia and hepatic MT can be used as biomarkers in assessing pollution status and pollution trends in water resources in Sri Lanka. In the present study, limited size range of Nile tilapia was used in biomarker studies as the body size could influence some biomarker measurements (Pathiratne et al 2008). Gender specific differences in the tested biomarkers in Nile tilapia were not evident in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…ChE activities in the brain and muscle homogenates were determined at 25 • C following the method of Ellman et al (1961) as a kinetic assay as described earlier (Pathiratne et al 2008). The enzyme source was prepared by homogenizing the brain or muscle tissue of individual fish separately in ice-cold, 0.1 M pH 8 phosphate buffer (20 mg tissue in 1 mL of buffer).…”
Section: Tissue Preparation For Biomarker Detectionmentioning
confidence: 99%
“…Serum SDH activity was determined at 25°C as described by Gerlach (1983) using D-fructose as the substrate. The ChE activities in the brain and muscle homogenates of individual fish were determined at 25°C using acetylthiocholine iodide as the substrate following the method of Ellman et al (1961) as described earlier (Pathiratne et al 2008). Microsomal and cytosolic fractions of liver tissues were prepared by differential centrifugation (Pathiratne et al 2009).…”
Section: Analysis Of Biomarker Enzymesmentioning
confidence: 99%
“…The enzyme source was prepared by homogenizing the brain or muscle tissue of individual fish separately (unless otherwise stated) in ice-cold 0.1 M pH 8 phosphate buffer (20 mg tissue in 1 ml buffer). ChE activities in the tissue homogenates were determined colorimetrically, following the method of Ellman et al (1961) as a kinetic assay by using a recording spectrophotometer (GBC Cintra 10e) fitted with a thermostated cuvette holder as described previously (Pathiratne et al 2008). Proteins in the tissue homogenate were determined following Lowry's method (Lowry et al 1951).…”
Section: Determination Of Che Activitymentioning
confidence: 99%